Finite element analysis of wedge and biconcave deformity in four different height restoration after augmentation of osteoporotic vertebral compression fractures - Xiao-Hua Zuo; Yin-Bing Chen; Peng Xie; Wen-Dong Zhang; Xiang-Yun Xue; Qian-Xi Zhang; Ben Shan; Xiao-Bing Zhang; Hong-Guang Bao; Yan-Na Si (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Purpose Biomechanical comparison of wedge and biconcave deformity of different height restoration after augmentation of osteoporotic vertebral compression fractures was analyzed by three-dimensional finite element analysis (FEA). Methods Three-dimensional finite element model (FEM) of T11-L2 segment was constructed from CT scan of elderly osteoporosis patient. The von Mises stresses of vertebrae, intervertebral disc, facet joints, displacement, and range of motion (ROM) of wedge and biconcave deformity were compared at four different heights (Genant 0–3 grade) after T12 vertebral augmentation. Results In wedge deformity, the stress of T12 decreased as the vertebral height in neutral position, flexion, extension, and left axial rotation, whereas increased sharply in bending at Genant 0; L1 and L2 decreased in all positions excluding flexion of L2, and T11 increased in neutral position, flexion, extension, and right axial rotation at Genant 0. No significant changes in biconcave deformity. The stress of T11-T12, T12-L1, and L1-L2 intervertebral disc gradually increased or decreased under other positions in wedge fracture, whereas L1-L2 no significant change in biconcave fracture. The utmost overall facet joint stress is at Genant 3, whereas there is no significant change under the same position in biconcave fracture. The displacement and ROM of the wedge fracture had ups and downs, while a decline in all positions excluding extension in biconcave fracture. Conclusions The vertebral restoration height after augmentation to Genant 0 affects the von Mises stress, displacement, and ROM in wedge deformity, which may increase the risk of fracture, whereas restored or not in biconcave deformity.